Plasma thrombin-antithrombin complex as a candidate biomarker for coronary slow flow - Jian-hong Mo; Bo Liang; Jing-tao Cen; Wan-ying Li; Yong-an Mo; Ming-cheng Tang; Dong Ye; Qiu-xia Long; Xun Hu; Xun Hu; Yuan-sheng Zhai; Yuan-sheng Zhai (Frontiers in Cardiovascular Medicine)
BackgroundCoronary slow flow (CSF), characterized by delayed coronary perfusion without significant coronary artery stenosis, remains a diagnostic challenge due to its elusive pathophysiology. This retrospective study aimed to evaluate the association between the thrombin-antithrombin (TAT) complex and CSF.Patients and methodsNinety-one CSF patients and 74 subjects with normal coronary flow were recruited in this cohort. Coronary artery blood flow was quantified using the thrombolysis in myocardial infarction frame count (TFC) method. Plasma TAT complex levels were measured via chemiluminescent immunoassay. Logistic regression analyses and a receiver operating characteristic (ROC) curve were performed to determine the predictive value of TAT for CSF.ResultsCompared with patients without CSF, patients with CSF showed higher plasma levels of TAT complex, total cholesterol, and low-density lipoprotein cholesterol, all of which were also positively correlated with TFC. However, multivariate logistic regression identified TAT as the only independent predictor of CSF after adjustment (OR: 1.71, 95% CI: 1.39–2.10, p < 0.001). More specifically, ROC analysis revealed that a plasma TAT complex levels of 3.875 ng/ml predicted CSF with a specificity of 89.2% and a sensitivity of 62.6%.ConclusionElevated plasma TAT complex levels are strongly associated with CSF and may serve as a candidate diagnostic biomarker.